A formação profissional em educação física no Pará e a aspiração discente - GORDO, Margarida do Espírito Santo Cunha (2013)
This article has the objective of recognizing the identity of Physical Education professionals that is being built in Physical Education undergraduate Programs, in the state of Pará, and whether these Programs will meet their students’ aspirations. The Political-Pedagogical Projects effective in the State University of Pará (UEPA) and in the Federal University of Pará (UFPA) – campus Belém and campus Castanhal - were analyzed; interviews were conducted with students attending the last semester of the Physical Education Program. As for the analysis of data gathered thereby, content analyzis techniques were adopted (according to MOREIRA; SIMÕES; PORTO, 2005), mainly to identify the aspirations of students. The study allowed to conclude that the Political-Pedagogical Projects relative to Physical Education Programs in the state of Pará establish the acquisition only of a full degree in Teaching,that for 100% of the students interviewed the attended course does not meet their expectations regardind professional training in the area, and that the official discourse reveal the fragility of professional identity in Physical Education in the State of Pará; it allowed as well to draw attention to the need that this training process be reviewed.